1990
DOI: 10.3109/17453679008993521
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyapatite coating enhances fixation of porous coated implants: A comparison in dogs between press fit and noninterference fit

Abstract: Intimate contact at the bone-porous surface interface is not always achievable in noncemented prosthetic implantation. We investigated the effect of hydroxyapatite (HA) coating on skeletal attachment in noninterference fit 4 weeks after implantation in 6 mature dogs. The pushout test of HA-coated implants surrounded by a 1-mm gap showed a twofold increased shear strength and fivefold increased shear stiffness compared with titanium alloy (Ti) coated implants. The fixation of Ti implants was reduced by two thir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
79
4
4

Year Published

1992
1992
2006
2006

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 185 publications
(93 citation statements)
references
References 29 publications
6
79
4
4
Order By: Relevance
“…Thus, as suggested by Page et al (2Y), relative movements at the fracture site lead both to the inhibition of angiogenesis and to the subsequent differentiation of cartilage. Whether the fibrocartilage found around the unstable HA-coated implants in the present study will be replaced later by bone by endochondral ossification is yet unknown, but stud--_ _ anchorage and bony ingrowth into HA-coated implants compared with porous coated Ti implants (35)(36)(37). This was confirmed by the present study concerning the stable implants that were unloaded to ensure rigid stability.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Thus, as suggested by Page et al (2Y), relative movements at the fracture site lead both to the inhibition of angiogenesis and to the subsequent differentiation of cartilage. Whether the fibrocartilage found around the unstable HA-coated implants in the present study will be replaced later by bone by endochondral ossification is yet unknown, but stud--_ _ anchorage and bony ingrowth into HA-coated implants compared with porous coated Ti implants (35)(36)(37). This was confirmed by the present study concerning the stable implants that were unloaded to ensure rigid stability.…”
Section: Discussionsupporting
confidence: 78%
“…Reduced bony ingrowth and weakened mechanical anchorage of the porous coated implant may occur if the bone stock is osteopenic (34), in the absence of initial contact between bone and implant (9, [35][36][37]40), if the pore size of the surface coating is too small (38), or with lack of initial mechanical stability between bone and implant (7,8,14,17,21, 30,40). However, hydroxyapatite (HA) coating has been demonstrated to increase bone ingrowth and anchorage strength of porous coated implants Experimental studies of cementless tibial components implanted into cadaver tibias have shown micromovements ranging between 200 and 500 pm at loads in the low physiologic range (6, 33,39,47).…”
Section: K Soballe Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors have reported that as little as 10-20% of a press-fit inserted prosthesis is in contact with the bone (Noble et al 1988, Schimmel andHuiskes 1988, Geesink 2002). Our previous work with gap implants has consistently shown abundant ongrowth of fibrous tissue, inferior bony ongrowth, and poor mechanical fixation (Soballe et al 1990, Elmengaard et al 2005. In previous studies, the titanium implant surface has been shown to be similar to that of commercially available prostheses with a plasma spray titanium coating (Soballe et al 1992(Soballe et al , 1993.…”
Section: Discussionmentioning
confidence: 99%
“…7 The use of calcium phosphate (CaP) coatings has also been shown to benefit the bone response during the initial healing period after implant insertion. 8 Various animal studies have proved that CaP-coated implants show greater bone contact than non-coated implants. 9,10 In addition to surface quality, growth factors can also stimulate bone healing around implants.…”
Section: Introductionmentioning
confidence: 99%